Pneumopericardium due to blunt trauma - Semerkant, Tolga; Duran, Ferdane Melike; Esme, Hıdır; Ateş, Arif; Doğan, Hasan; Karaduman, Mehmet (Journal of Surgery and Medicine, 2022)
Pneumopericardium is the presence of gas in the pericardial sac. Its etiology includes chest trauma, iatrogenic causes, thoracic surgery, and mechanical ventilation, and it is mostly asymptomatic. However, pneumopericardium can also be fatal because it can cause cardiac tamponade. All surgeons dealing with thoracic trauma should be aware of this pathology. A case of a 30-year-old patient presenting with pneumopericardium due to blunt trauma who was evaluated in the emergency department at our hospital is presented.